Effect of Meaningfulness on Learning Syntactic Units. - Gallagher, Joseph W. (American Journal of Mental Deficiency, 1970)
The article presents a study examining the influence of meaningfulness and non meaningfulness on the learning of syntactic word pairs with institutionalized mentally retarded and normal children. Through a paired-associate technique, subjects were presented with a list of meaningful and nonmeaningful pairs. Results showed no differences between normal children and retardates for the meaningful pairs. Also, normal children learned the meaningful pairs with lesser errors than retarded children.